Character Building Through Differentiated Learning of Islamic Religious Education in the Digital Era - Ihwanah, Al; Idi, Abdullah; Karoma, Karoma; Afifah, Ni'mah; Diana (Ta'dib, 2024)
This study aims to explore the implementation of differentiated learning in Islamic Religious Education (PAI) as a means of character development in the digital era at MI Al-Khoiriyah Banyuasin, South Sumatra. This study employs a descriptive qualitative approach aimed at analyzing the processes and dynamics of implementing differentiated learning in building students' character through Islamic Religious Education (PAI) in the digital era. This study employs a case study design to examine the implementation of differentiated learning in elementary schools. Data were collected through classroom observations, in-depth interviews with teachers, school principals, and students, as well as document analysis, including lesson plans and student work. The data were analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. This study concludes that the implementation of differentiated learning in Islamic Religious Education (PAI), supported by digital technology, effectively enhances students' character development. For example, through personalized learning tasks and digital platforms, students demonstrate improved discipline, responsibility, and collaboration skills, reflecting stronger character values. The use of digital media, such as educational apps and videos, enhances the understanding of religious values and fosters positive attitudes, such as discipline, empathy, and tolerance. This approach allows students to develop according to their potential, making character internalization more effective and relevant.